Implementation of Student Group Discussion Method to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 091566 Bah Jambi - Hidayati, Sri; Dirmaya, Eva (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to analyze the effectiveness of the application of group discussion methods for students in increasing their piety to Allah SWT on the material of commendable morals in class VI of SD Negeri 091566 Bah Jambi. This study was motivated by the need to improve students' understanding and appreciation of commendable moral values, which are expected to have a positive impact on increasing their piety. This study uses a Classroom Action Research approach with a cycle model consisting of planning, action, observation, and reflection, and is supported by qualitative data obtained through in-depth interviews with students and teachers, as well as participant observation in the classroom. The subjects of the study were class VI students and Islamic Religious Education teachers at SD Negeri 091566 Bah Jambi. The results of the study showed that the application of group discussion methods significantly improved students' understanding of the concepts of commendable morals such as honesty, trustworthiness, and compassion, and increased their awareness of the relationship between commendable morals and piety to Allah SWT. Students become more active and enthusiastic in learning, able to collaborate in groups, and show increased ability in expressing opinions and arguing politely. Group discussions also provide space for students to reflect on and internalize the meaning of piety in the context of everyday life through the exchange of experiences and perspectives between students. In addition, Islamic Religious Education teachers also show improvements in their ability to facilitate discussions and provide guidance to students.